GRADE guidance 40: The GRADE evidence-to-decision framework for environmental and occupational health - Emily Senerth; Paul Whaley; Elie Akl; Brandy Beverly; Pablo Alonso-Coello; Andrew Rooney; Holger J. Schünemann; Kristina A. Thayer; Katya Tsaioun; Rebecca L. Morgan (Environment International)
Objective: To provide guidance for the use of the Grading of Recommendations Assessment, Development and Evaluation (GRADE) Evidence-to-Decision (EtD) framework for environmental and occupational health (EOH). Study design and setting: We conducted a systematic review and narrative synthesis of published and public EOH decision frameworks, followed by a modified Delphi process leading to development of a draft GRADE EtD framework for EOH. We pilot tested the provisional framework through a virtual workshop series, which further informed guidance for the framework’s application. We presented a summary of the results to all attendees of the GRADE Working Group meeting for feedback in July 2022 and November 2022, and for approval in May 2023. Results: Consistent with existing GRADE EtD frameworks, the EtD framework for EOH includes a scoping and contextualization process and twelve assessment criteria. Modifications to the existing EtD frameworks include: consideration of the socio-political context when making judgments about the priority of the problem and feasibility of different alternatives; the addition of timing when making judgments about benefits and harms, the balance of effects, and feasibility; broadening of the equity criterion to include considerations beyond health equity; and more explicit accommodation of variable or conflicting stakeholder views when considering values and acceptability. The new EtD framework is also accompanied by a user guide intended to support its implementation in the EOH context. Conclusion: Policymakers, regulators, and other stakeholders may use this GRADE EtD framework to approach decision-making about environmental and occupational exposures and interventions.